Multiple Primary Malignancies: A Clinicopathological Profile of Patients at a Tertiary Center of North India—A Retrospective Hospital-Based Observational Study - Abdul W. Mir; Shaheena Parveen; Ifrah Ahmad; Shah Naveed; Syed N. Ahmad; Mir M. Hussain; Nazir A. Dar (Indian Journal of Medical and Paediatric Oncology)
Introduction The incidence, prevalence, as well as survival of cancer patients, is increasing day by day due to the use of screening and improved diagnostic modalities. Simultaneously, the development of multiple primary malignancies (MPMs) in cancer survivors is not uncommon in recent years, because of an improved understanding of biology and effective management of cancer in the form of local (i.e., surgery/radiotherapy) and systemic (chemotherapy/targeted therapy) treatment, leading to improved survival and subsequent development of more malignancies. The study was conducted to describe the clinicopathological profile of patients diagnosed with MPMs.